PENGARUH METODE ROLE PLAYING TERHADAP KOMUNIKASI INTERPERSONAL SISWA KELAS IV SD NEGERI 31 PANGKALPINANG - Nur Apriani Rahmat; M.Iqbal Arrosyad; Yurdayanti (STKIP Subang, 2025)
The development of peer interaction abilities in elementary students can be significantly shaped through innovative educational strategies, one of which, explored in this study, is the Role-Playing method. This investigation focused on determining the degree to which this approach enhances the interpersonal skills of fourth-grade learners at SD Negeri 31 Pangkalpinang. The research employed a mixed-method design encompassing the entire fourth-grade cohort of 35 students, sampled using a saturated sampling procedure. Students in the experimental condition received lessons via Role-Playing. Questionnaire responses and observational data were collected and analyzed with the Shapiro–Wilk and Paired Sample T-tests. The outcomes demonstrated a meaningful elevation in interpersonal communication, as indicated by an increase in post-test scores to 75.71 from a pre-test score of 54.97. The statistical significance of the improvement was confirmed by a t-value of 10.039, above the critical t of 2.030, at p < 0.05. Observations further showed an average activity level of 72.63, classified as actively engaged. Overall, the study confirms that the Role-Playing approach exerts a significant beneficial effect on fourth graders’ interpersonal interactions at SD Negeri 31 Pangkalpinang.